2010
DOI: 10.3844/ajidsp.2010.29.33
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotics Susceptibility of Uropathogens in Patients from a Rural Environment, Tamilnadu

Abstract: Problem statement: Urinary Tract Infections (UTIs) in human, rural environment cause significant morbidity due to insanitary condition, lack of knowledge of personal hygiene, lack of patient's compliance and economic burden. In our study, the bacterial etiologies and the resistance patterns found in human with serious UTIs and selecting optimal antimicrobial therapy. Approach: A total of 105 patients first morning mid stream urine samples, culture was done by the calibrated loop technique delivering 0.001 mL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 18 publications
(20 reference statements)
8
30
1
Order By: Relevance
“…The reason for the higher prevalence of CoNS in males is not clear, though lack of circumcision, receptive anal intercourse and HIV infection recognised as risk factor for males (Orrett & Davis 2006). The study revealed that females (65.3%) were more susceptible to UTI than males (34.7%), which is also similar to other studies (Dimitrov et al 2003, Akram et al 2007, Arjunan et al 2010, Manjunath et al 2011, Alzohairy & Khadri 2011, Acharya et al 2011. The increased incidence of the urinary tract infection in women is conditioned by favouring anatomic factors, by hormonal changes and by the urodynamic disturbance occurring with age (Bobos et al 2010).…”
Section: Table 1 Distribution Of Uropathogens Among Males and Femalessupporting
confidence: 80%
See 1 more Smart Citation
“…The reason for the higher prevalence of CoNS in males is not clear, though lack of circumcision, receptive anal intercourse and HIV infection recognised as risk factor for males (Orrett & Davis 2006). The study revealed that females (65.3%) were more susceptible to UTI than males (34.7%), which is also similar to other studies (Dimitrov et al 2003, Akram et al 2007, Arjunan et al 2010, Manjunath et al 2011, Alzohairy & Khadri 2011, Acharya et al 2011. The increased incidence of the urinary tract infection in women is conditioned by favouring anatomic factors, by hormonal changes and by the urodynamic disturbance occurring with age (Bobos et al 2010).…”
Section: Table 1 Distribution Of Uropathogens Among Males and Femalessupporting
confidence: 80%
“…Nitrofurantoin was also found as the most effective antimicrobial in UTI caused by E. coli from studies in Nepal (Karki et al 2004, Shrestha et al 2007, Sharma et al 2011, Rijal et al 2012) and rest of the world (Sahm et al 2001, Jamie et al 2002, Alos et al 2004, Okonko et al 2009, Behroozi et al 2010, Eryilmaz et al 2010. However, Akram et al (2007), Kausar et al (2009), andArjunan et al (2010) were reported higher rate of E. coli resistance to nitrofurantoin. In case of the present study, nitrofurantoin was found to be the most effective antimicrobial.…”
Section: Table 1 Distribution Of Uropathogens Among Males and Femalesmentioning
confidence: 96%
“…Acinetobacter and Citrobacter, both common pathogens in UTI, were however not isolated in this present study. Such findings have been documented elsewhere [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Furthermore, while most other workers elsewhere have reported the involvement of Klebsiella as the second most important pathogen in UTI cases [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] , our present study in this area shows a far greater involvement of gram-positive cocci than Klebsiella.…”
Section: Discussionsupporting
confidence: 67%
“…While ciprofloxacin and ofloxacin are the most extensively used fluoroquinolones for the treatment of UTIs the emergence of resistance for fluoroquinolones is based on several factors [15,19,29,30] . Resistance to ciprofloxacin has emerged in a variety of genera belonging to the family Enterobacteriaceae.…”
Section: Discussionmentioning
confidence: 99%
“…typically multiply at the opening of the urethra and folding up to the bladder. On the other hand bacteria much less often spread to the kidney from the blood stream [4].Recurrent signs and symptoms of the infection need to repeat the treatment and misuse the antibiotics clinically lead to an increasing in multi-drug resistance bacteria which also causing the spread of bacterial resistant strains, resulting in very high rates of morbidity rather than cost-effective related with its treatment [5]. Untreated infections may be risen to the upper urinary tract and produce fever, chills, increase burning pain on urination, and side pain.…”
Section: Introductionmentioning
confidence: 99%